Gaussian processes for time-series modelling. - Roberts, S; Osborne, M; Ebden, M; Reece, S; Gibson, N; Aigrain, S (2013)
In this paper, we offer a gentle introduction to Gaussian processes for time-series data analysis. The conceptual framework of Bayesian modelling for time-series data is discussed and the foundations of Bayesian non-parametric modelling presented for Gaussian processes. We discuss how domain knowledge influences design of the Gaussian process models and provide case examples to highlight the approaches.